Enantioselective Dihalogenation of Alkenes. Issue 14 (7th January 2021) - Bock, Jonathan; Guria, Sudip; Wedek, Volker; Hennecke, Ulrich
Abstract: The dihalogenation of alkenes is one of the classic reactions in organic chemistry and a prime example of an electrophilic addition reaction. The often observed anti ‐selectivity in this addition reaction can be explained by the formation of a haliranium‐ion intermediate. Although dihalogenations have been studied for more than a century, the development of reagent‐controlled, enantioselective dihalogenation has proved to be very difficult. Only recently, significant progress has been achieved. In this review, an overview on current method development in enantioselective dihalogenation is provided and mechanistic aspects that render this transformation challenging are discussed. Abstract : Taking control : Dihalogenation is one of the most typical electrophilic addition reactions to alkenes. Nevertheless, the development of reagent‐controlled asymmetric versions of this reaction has proven to be a formidable challenge and general methods are not yet available. This review summarizes the current state‐of‐the‐art for this reaction and discusses relevant mechanistic features for future catalyst development.